Infestation and Management of the Leaf Roller (Lamprosema indicata Fab.) in Soybean (Glycine max L.) (Bangladesh Journal of Agricultural Research, 2012)
Infestation and management of leaf roller of soybean were studied in the field   and laboratory of the Oilseed Research Centre (ORC), Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur during the rabi seasons of 2007-08 and 2008-09. Leaf roller infestation was observed in the 3rd week of January at the vegetative and flowering stages (45-60 days after sowing=DAS) of the crop and continued up to pre-maturity period (80-85 DAS). The highest leaf   roller population (0.9 and 1.00/plant in 2008 and 2009, respectively) and infestation (90% plant in 2008 and 95% plant in 2009) were recorded in the last week of February at the pod formation stage of the crop (65-70 DAS). Among the treatments, hand picking technique reduced the highest plant and leaf (98%) infestation. The highest seed yield (1300 kg/ha) was obtained from Diazinon 60 EC treated plots, followed by hand picking+neem seed extract treated plot (1280   kg/ha). The highest BCR (3.00) was obtained from the hand picking technique plots followed by Diazinon 60 EC treated plots (2.66). DOI: http://dx.doi.org/10.3329/bjar.v37i1.11171 Bangladesh J. Agril. Res. 37(1): 19-25, March 2012